Anthropology and image in colonial contexts: the scientific expedition to Spanish territories in the Gulf of Guinea (1948) - Luis Calvo Calvo (Culture & History Digital Journal, 2023)
Spanish Guinea, as the largest Spanish colonial territory in sub-Saharan Africa, was the object of scientific attention by several official Spanish institutions such as the Institute of African Studies (IDEA) and the Ethnological and Colonial Museum of Barcelona (MECB). Both were interested in describing and documenting the colony’s ways of life and sponsored the 1948 Expedition to Spanish Guinea that inaugurated other MECB study trips during the 1950s. Images, in various formats (drawing, photography, etc.), played a significant role in these investigations, becoming a major instrument to describe the colony’s past and present. In this way, it not only contributed to consolidating the Spanish colonial vision and actions but also helped to confirm, scientifically, the subordination of the indigenous populations to the metropolitan colonial power. This article presents the details of the 1948 Expedition as well as the visual record generated. Finally, some reflections are made on the role of images in this context.